The Anti-Osteoporotic Drug Preferences of Physiatrists: A Multicenter Descriptive Study - Kutsal, Yesim Gokce; Ozdemir, Oya; Caliskan, Asli; Inanici, Fatma; Karahan, Sevilay; Dogan, Asuman; Yazgan, Pelin (Galenos Yayincilik, 2012)
Aim: The purpose of this multicenter descriptive study is to determine the preferences of physiatrists in our country for anti-osteoporotic drugs in patients with primary and secondary osteoporosis. Materials and Methods: This study was carried out in 10 provinces of Turkey. The diagnosis of osteoporosis was based on World Health Organization criteria using dual-energy x-ray absorptiometry. Patients with a spine and/or hip T-score <=-2.5 were considered as osteoporotic. 714 patients over 18 years old with primary or secondary osteoporosis were included in the study. In addition to socio-demographic characteristics and chronic use of medications and/or additional systemic diseases that cause secondary osteoporosis were questioned and antiosteoporotic drugs that are recommended by their physicians were recorded. Results: The physicians' preferred vitamin D and calcium as the prior treatment both in primary and secondary osteoporosis. The most commonly used anti-osteoporotic agent was alendronate from the biphosphonate group. It was followed by ibandronate, risedronate, strontium ranelate, calcitonin, zoledronate, raloxifene, parathyroid hormone (PTH) and hormone replacement therapy (HRT) in the primary osteoporosis and risedronate, ibandronate, calcitonin, strontium ranelate, zoledronate, PTH, HRT and raloxifene in the secondary osteoporosis, respectively. Conclusion: The physician should choose the most suitable treatment for the patient based on fracture risk, medical history, previous treatments for osteoporosis, concomitant diseases, treatment-induced risks and benefits, and the relation between financial cost and potential benefit.
Fiziatristlerin antiosteoporotik i?laç tercihleri: Çok merkezli tanimlayici araştirma
Keywords: Osteoporosis; medicine; treatment